Raman spectroscopy and cytopathology of oral exfoliated cells for oral cancer diagnosis. Issue 18 (21st September 2015) - Sahu, Aditi; Tawde, Sneha; Pai, Venkatesh; Gera, Poonam; Chaturvedi, Pankaj; Nair, Sudhir; Krishna, C. Murali
<x xml:space="preserve">Abstract</x> Raman spectroscopy coupled with cytopathology of oral exfoliated cell specimens can differentiate between healthy and tumor groups.